2011
DOI: 10.1118/1.3611043
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of the storage phosphor europium doped potassium chloride for radiation therapy dosimetry

Abstract: Systematic studies of KCl:Eu2+ material are important for understanding how the material can be optimized for radiation therapy dosimetry purposes. The data presented here indicate that KCl:Eu2+ exhibits strong radiation hardness and lends support for further investigations of this novel material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Figure 1 shows that the sensitivity increases by 15% with a cumulative dose of 5 kGy and then decreases with higher cumulated doses. These results correlate well with previous results [4]. Batentschuk et al [6] also reported a slight increase in PSL intensity for CsBr:Eu 2+ .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Figure 1 shows that the sensitivity increases by 15% with a cumulative dose of 5 kGy and then decreases with higher cumulated doses. These results correlate well with previous results [4]. Batentschuk et al [6] also reported a slight increase in PSL intensity for CsBr:Eu 2+ .…”
Section: Resultssupporting
confidence: 93%
“…Pellets of KCl:Eu 2+ (1 mm thick, 6 mm diameter) with 0.05 mole % Eu, were made using a hydraulic press using a procedure described earlier [4]. The XRLM4 beam line at the Center for Advanced Microstructures and Devices (CAMD) synchrotron facility at Louisiana State University was used for high dose irradiation of samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work (Han et al , 2009; Driewer et al , 2011) has shown that KCl:Eu 2+ has great potential for use in megavoltage radiation therapy dosimetry because this material exhibits excellent storage performance and is reusable due to strong radiation hardness. Hansel et al (Hansel et al , 2014; Hansel et al , 2013) report that KCl:Eu 2+ samples provide excellent signal even after they were given doses of up to 200 kGy at the Louisiana State University Synchrotron facility.…”
Section: Introductionmentioning
confidence: 99%